The metier and scope of textile design: an overview in Brazil (Revista de Ensino em Artes, Moda e Design, 2023)
Textile design, which in Brazil is often associated with print design, consists of a wide field of activities along the textile production chain. This study aimed at characterizing the metier and list the specifications of textile design in the 21st century, from the descriptions presented in profession guides and career manuals, to the theoretical definitions of surface design in terms of textiles, as well as terms adopted by the Brazilian market, having concluded that, as the activity specializes in certain links in the production chain, new areas of action emerge and the need for synergy between the various designers participating in this long chain that ranges from textile fibers to the manufacture of the final product.
Keywords: textile design; surface design; print design